Development of enhanced fitness Salmonella Live Vector Carrier vaccine by using Toxoplasma gondii antigens as a model candidate - Loh, Fei Kean (2020)
Live Salmonella Typhi vector has been a highly versatile vaccination platform to invade internal effector lymphoid tissues to elicit both mucosal and systemic immunity. Its proficiency in safeguarding itself within intracellular niche has made it compatible to induce the desirable cell-mediated immunity against obligate intracellular parasite, Toxoplasma gondii. The parasite can infect almost all mammals, thus posing threats to public health and economic losses. T. gondii vaccine research is of great medical value due to the lack of effective toxoplasmosis vaccine. In the present work, T. gondii antigens were cloned into a low-copy stabilised plasmid and integrated into a growth-dependent chromosome locus via lambda-red homologous recombination for heterologous expression within a live S. Typhi vector. The incorporation of an osmolarity-regulated promoter enabled the control of gene transcription and the clyA export protein was included to translocate the antigen out of the cytoplasm. These combination of construction strategies have enhanced the growth fitness of recombinant S. Typhi bivalent vaccine strains. Four live recombinant S. Typhi bivalent vaccine strains combining tachyzoite-specific surface antigen 1 (SAG1), bradyzoite-specific antigen 1 (BAG1) or all-stages dense granule antigen 2 (GRA2) against different life stages of T. gondii were constructed. The recombinant S. Typhi bivalent vaccine strains displayed healthy growth fitness and readily expressed the encoded T. gondii antigens. When administered in vivo, these recombinant S. Typhi bivalent vaccine strains successfully induced both humoral and cellular immunity in the immunised BALB/c mice, and extended mice survival against virulent T. gondii. In particular, the CVD910-BS group (expressing BAG1 in chromosome and SAG1 in plasmid) demonstrated strong humoral immunity response with significant elevation in IgG titres as tested by enzyme-linked immunosorbent assay (ELISA). Compared to control, all mice given the recombinant S. Typhi bivalent vaccine strains presented higher percentages of CD4+ and CD8+ T cells as analysed by fluorescence-activated cell sorting (FACS), with secretions of cytokine IFN-ɣ, IL-2, and IL-10 as determined by ELISA. The overall results suggested that only CVD910-GS strain (expressing GRA2 in chromosome and SAG1 in plasmid) achieved both satisfactory growth fitness and antigen expression, generated high cellular immunogenicity and memory responses leading to the longest survival of infected mice in the challenge study. In conclusion, this study demonstrated the importance of enhancing live vector fitness to sustain heterologous antigen expression, which consequently elicited robust immune responses to provide effective protection against the targeted pathogen. In future perspective, the recombinant S. Typhi vaccine strains can be potentially developed into combination or multivalent vaccine strains against diverse range of pathogens.